Search for cryptic subtelomeric aberrations in patients with non-classical Marinesco-Sjögren phenotype - Roos, Andreas; Schwanitz, Gesa; Diepolder, Irmgard; Senderek, Jan; Eggermann, Katja (Journal of Pediatric Neurology, 2012)
Marinesco-Sjögren syndrome (MSS) is a multiorgan disorder firstly described in 1931 by Gheorge Marinescu. During the last seven decades, research into the clinical picture of MSS has led to the description of varying MSS phenotypes and since 2005, it is known that mutations within the SIL1 gene cause MSS in a part of these patients. Among these “SIL1-related MSS cases”, “classical and non-classical phenotypes” are distinguished. All “SIL1-related MSS cases” show at least an ataxia due to cerebellar atrophy, congenital or infantile cataracts and a progressive myopathy as well as mental impairment (“classical MSS phenotype”). Additional clinical features are for example in some cases short stature, hypogonadism, scoliosis, nystagmus and strabismus (“non-classical MSS phenotype”). However, the primary pathology has remained unknown in non-SIL1-related MSS cases. As the clinical features detected in “classical MSS phenotype” and “non-classical MSS phenotype” may also be associated with cryptic subtelomeric rearrangements and as a frequent localization of for example cataract-related genes/loci within these regions is proven, we performed subtelomere screening in a series of 23 patients with “non-SIL1-related non-classical MSS phenotypes” presenting with at least three features like early cataracts, mental retardation, brain malformations, muscular hypotonia, growth retardation and skeletal abnormalities. Karyotype and the SIL1 coding sequence were normal in all cases. Subtelomere screening by multiplex ligation-dependent probe amplification did not identify any subtelomeric imbalances. Therefore, a causative role of these regions in manifesting "non-SIL1-related non-classical MSS phenotypes" seems to be unlikely.
Keywords: Marinesco-Sjögren syndrome; subtelomere-screening; mental retardation; congenital cataract; ataxia; muscular hypotonia